On the global asymptotic stability and oscillation of solutions in a stochastic business cycle model. Issue 11 (1st November 2016) - Deng, Guifeng; Chen, Guoting; Qian, Lili
Abstract : We discuss a second order nonlinear stochastic difference equation which is constructed of a business cycle model with organized labor considered. A global asymptotic mean square stability criterion is obtained by Lyapunov function method. We also prove a theorem on the almost sure oscillation of the solutions for the difference equation with state-independent stochastic perturbations.